Impacts of COVID-19 on travel mode preferences in Klang Valley - Nor Aznirahani Mhd Yunina,; Imran Yussof,; Sima, Ho Jen (Penerbit Universiti Kebangsaan Malaysia, 2022)
Change in activity patterns and travel behaviour were seen worldwide as a response to the COVID-19 pandemic. This is mainly due to the restrictive measures imposed by the government and perception of own safety or commitment in reducing the spread of the disease. However, with or without the restrictive measures, people still have various needs to travel. Thus, this study was initiated to understand the changes in travel behaviour due to the COVID-19 pandemic. An online questionnaire survey, including questions related to purpose of travel, transport mode choice, distance and frequency of trip was conducted. Findings from this study revealed that there is a significant change in activity pattern and travel behaviour, before and during the COVID-19 pandemic. Based on the 460 responses received, it is known that mode shifts, from public transportation to private vehicles, occurred mainly due to pandemic related concerns. This study reveals that people perceived public transportation as a potential risk for exposure of the COVID-19 virus, while private vehicles, bicycles and walking are viewed as the safest mode of transport during the pandemic. Gender, age group, vehicle ownership, marital status and purpose of travelling had significant impact on the mode choice during the pandemic. Based on these findings, it is hoped that rail and bus transport service providers will be able to plan measures and further encourage the usage of the rail and bus transport services post-pandemic.